Filosofia “more geometrico” e metafisica della sostanza. Husserl e l’oggettivismo di Cartesio - Trizio, Emiliano (Bollettino Filosofico, 2024)
This article approaches Husserl’s critique of Descartes by focusing on the issue of the scientificity of philosophy. In particular, it consists in an attempt to answer the following three questions: 1) What is the historical origin of the unprecedented form of objectivism that characterizes Descartes’ philosophy, and, after him, the entire modern rationalist tradition? 2) How did this form of objectivism shape the outcomes of Descartes’ thought, and caused him to miss the goal of a genuinely scientific universal philosophy? 3) How did Descartes’ objectivism become intertwined with a metaphysics based on the concept of substance, i.e., a metaphysics that transcendental phenomenology has the task of overcoming? Keywords: Descartes, Husserl, Metaphysics, Objectivism, Substance